Method for Colorimetric and Photothermal Dual-Mode Detection of Acrylamide in Coffee Based on MXene / MOFs Nanozymes
By preparing Mxene@Mn/Fe-MIL-NH2 nanoenzyme, combined with colorimetric and photothermal detection, the high sensitivity detection problem of acrylamide in coffee was solved, and high sensitivity and specific detection effect was achieved.
Patent Information
- Application Number
- CN202510630535.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-07-11
- Estimated Expiration
- 2045-05-16
AI Technical Summary
The prior art is difficult to detect acrylamide in coffee matrix with high sensitivity and accurate amounts, and the colorimetric method is greatly disturbed by the complexity and color of the coffee matrix.
Two-dimensional metal-organic frame nanosheets Mn/Fe-MIL-NH2 were synthesized by solvent-thermal method, and self-assembled with MXene to form Mxene@Mn/Fe-MIL-NH2 nanoenzymes. Using its peroxidase-like activity and photothermal properties, acrylamide was detected under near-infrared light irradiation, combining colorimetric and temperature sensing.
The high sensitivity dual-mode detection of acrylamide in coffee is realized, with the detection limits of 0.03μg/mL and 0.01μg/mL, eliminating interference from coffee matrix, high detection accuracy and simple operation.
Smart Images

Figure CN120142204B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of chemical analysis and detection, and particularly relates to a method for colorimetric and photothermal dual-mode detection of acrylamide in coffee based on MXene / MOFs nanozymes. Background Art
[0002] Acrylamide (AM) is a potentially carcinogenic substance with neurotoxicity generated during the thermal processing of foods. As one of the world's three major beverages, coffee has biological functions such as reducing blood sugar and lipids and neuroprotection. A series of reactions such as Maillard and caramelization occur during the high-temperature roasting stage of green coffee beans, and a large number of new compounds produced endow coffee with a unique flavor. However, the Maillard reaction is also the main pathway for the formation of the food contaminant - acrylamide. The per capita daily intake of caffeine is too high globally, making it one of the high-contribution foods for acrylamide. Therefore, how to effectively take measures to reduce the mass fraction of acrylamide in coffee beverages has become a key issue of global concern, and highly sensitive and accurate quantification of acrylamide in coffee is a prerequisite for studying the formation mechanism and inhibitory effects of AM. Currently, various instrumental analysis methods such as HPLC, LC-MS / MS, and GC-MS have been used to detect the AM content in foods. Although there are reports on the rapid detection of AM by colorimetry and fluorescence methods, due to the complex coffee matrix, especially the relatively dark color of the extract, it causes great interference to the determination.
[0003] In recent years, photothermal analysis platforms based on temperature signal readout have been widely studied due to their simplicity, convenience, and on-site practicality in different sensing fields. Interestingly, in addition to being used for colorimetric analysis in the ultraviolet-visible spectrum, as the main substrate of peroxidase, the oxidation of 3,3',5,5'-tetramethylbenzidine (TMB) (oxTMB) also shows absorption in the near-infrared (NIR) spectrum and exhibits a strong NIR laser (808 nm)-triggered photoconversion efficiency for highly sensitive quantitative photothermal detection. Summary of the Invention
[0004] The present invention provides a method for colorimetric and photothermal dual-mode detection of acrylamide in coffee based on MXene / MOFs nanozymes. In the method of the present invention, LiF and HCl are used to etch Ti3AlC2 to obtain Mxene, and two-dimensional metal-organic framework nanosheets Mn / Fe-MIL(53)-NH2 are synthesized by a solvothermal method. Then, the composite nanomaterial Mxene@Mn / Fe-MIL-NH2 is prepared by self-assembly. Mxene@Mn / Fe-MIL-NH2 has peroxidase-like activity and photothermal properties. Under the irradiation of near-infrared light at 808 nm, its peroxidase-like activity is improved. The addition of acrylamide accelerates the rate of Mxene@Mn / Fe-MIL-NH2 oxidizing the substrate TMB, and at the same time, the temperature of the oxidized TMB with photosensitive properties is also increased. Thus, a new method for highly sensitive and selective detection of acrylamide by colorimetry and temperature sensing is established, with detection limits of 0.03 μg / mL and 0.01 μg / mL respectively. Especially as an effective temperature sensing, it can significantly eliminate the interference brought by the coffee matrix. The method has the characteristics of high sensitivity, strong specificity, simple operation, and rapidity.
[0005] The method for colorimetric and photothermal dual-mode detection of acrylamide in coffee based on MXene / MOFs nanozymes of the present invention is as follows:
[0006] (1) Add 1-2 g of LiF and 20-40 mL of 9 mol / L HCl to a polytetrafluoroethylene beaker, stir at 400-600 rpm for 1-1.5 h, then slowly add 1-2 g of Ti3AlC2. After adding and mixing evenly, keep stirring at a temperature of 35 °C for 48 h, centrifuge at 3500-4000 rpm for 10-15 min, wash with pure water until the pH is about 5, and freeze-dry to obtain Mxene;
[0007] (2) Dissolve 2-3 mmol of FeCl3·6H2O and 4-6 mmol of Mn(CH3COO)2·4H2O in 20-40 mL of DMF, denoted as solution A; at the same time, dissolve 2-3 mmol of NH2-BDC (2-aminoterephthalic acid) in another 20-40 mL of DMF, denoted as solution B; then, slowly add solution A to solution B, stir and mix evenly, put the mixed solution into a Teflon autoclave, heat at 120-140 °C for 8-10 h, naturally cool, centrifuge at 6000-8000 rpm for 5-10 min to obtain a light brown precipitate. Wash the precipitate 3-4 times with DMF and absolute ethanol respectively, centrifuge at 6000-8000 rpm for 5-10 min, and dry the collected product at 80 °C for 12-24 h to obtain Mn / Fe-MIL-NH2;
[0008] (3) Mix Mxene and Mn / Fe-MIL-NH2 in a mass ratio of 1:3 - 4 and disperse them in 50 - 80 mL of pure water. Stir for 6 - 8 h at room temperature to obtain Mxene@Mn / Fe-MIL-NH2 nanozyme;
[0009] (4) Add the Mxene@Mn / Fe-MIL-NH2 nanozyme solution to acrylamide (AM) solutions with different gradient concentrations respectively. Then add 3,3',5,5'-tetramethylbenzidine (TMB) and H2O2 to generate a blue oxidation product. Dilute to 3 mL with pH 7.0 phosphate buffer solution, shake well, let stand for 5 - 10 min, and measure the absorbance at a wavelength of 654 nm to determine the linear relationship between the AM concentration and the absorbance value, and obtain the regression equation;
[0010] (5) Add the Mxene@Mn / Fe-MIL-NH2 nanozyme solution to acrylamide solutions with different gradient concentrations respectively. Then add 3,3',5,5'-tetramethylbenzidine (TMB) and H2O2 to generate a blue oxidation product. Dilute to 3 mL with pH 7.0 phosphate buffer solution, shake well. After irradiating the reaction solution with 808 nm NIR laser for 4 - 6 min, immediately use a portable pen-type digital thermometer to record the temperature and calculate the temperature change value ΔT. Determine the linear relationship between the AM concentration and the temperature change value ΔT, and obtain the regression equation, where ΔT = T - T0, and T and T0 are the temperatures of the reaction solution after and before laser irradiation respectively;
[0011] (6) Operate the test sample solution according to steps (4) and (5), measure the absorbance value and the temperature change value ΔT, substitute them into the regression equation, and obtain the acrylamide content in the test sample solution.
[0012] The concentration of the Mxene@Mn / Fe-MIL-NH2 solution is 30 μg / mL, the addition amount is 50 - 100 μL, the concentration of TMB is 0.2 mmol / L, the addition amount is 50 - 100 μL, the concentration of H2O2 is 2 mmol / L, the addition amount is 50 - 100 μL, and the power of 808 nm NIR is 1.5 - 2.0 W / cm 2 。
[0013] The advantages of the present invention are as follows:
[0014] 1. The present invention synthesizes two-dimensional metal-organic framework nanosheets Mn / Fe-MIL-NH2 with excellent photothermal conversion performance, many accessible active sites, mesoporous / macroporosity and faster electron transfer. The composite nanomaterial Mxene@Mn / Fe-MIL-NH2 is prepared in a self-assembled manner. Through the synergistic effect of the electron transfer process and the generation of ·OH, Mxene@Mn / Fe-MIL-NH2 exhibits excellent peroxidase-like activity and photothermal performance under neutral conditions. Importantly, acrylamide shows a specific response by specifically binding to Mxene@Mn / Fe-MIL-NH2, and then enhances the intrinsic peroxidase-like activity, providing a promising alternative method for simple, rapid, specific, sensitive and background-free photothermal detection of acrylamide;
[0015] 2. Since acrylamide increases the peroxidase activity of the nanozyme, and 808nm NIR laser irradiation further increases the peroxidase-like activity, resulting in a larger absorbance and temperature difference in the detection system, highly sensitive dual-mode detection of acrylamide is achieved, with detection limits of 0.03 μg / mL and 0.01 μg / mL respectively. In particular, the spiked recovery rate of photothermal detection of acrylamide in coffee reaches 92.33% - 100.34%, and the detection accuracy of the system is relatively high. Brief Description of the Drawings
[0016] Figure 1 Figure 1 is the TEM image of the Mxene nanozyme synthesized in Example 1;
[0017] Figure 2 is the TEM image of the Mxene@Mn / Fe-MIL-NH2 nanozyme synthesized in Example 1;
[0018] Figure 3 is the UV-visible absorption spectra of Mxene@Mn / Fe-MIL-NH2 + H2O2 + TMB and Mxene@Mn / Fe-MIL-NH2 + AM + H2O2 + TMB in Example 1;
[0019] Figure 4 Figure 4 is the Michaelis-Menten equation of the Mxene@Mn / Fe-MIL-NH2 nanozyme in Example 1 under the conditions of (a) fixing the concentration of H2O2 and changing the concentration of TMB, and (b) fixing the concentration of TMB and changing the concentration of H2O2;
[0020] Figure 5 Figure 5 is the Michaelis-Menten equation of the Mxene@Mn / Fe-MIL-NH2 nanozyme in the presence of AM under the conditions of (a) fixing the concentration of H2O2 and changing the concentration of TMB, and (b) fixing the concentration of TMB and changing the concentration of H2O2;
[0021] Figure 6Results of free radical capture during the catalytic process of Mxene@Mn / Fe-MIL-NH2;
[0022] Figure 7 For the Mxene@Mn / Fe-MIL-NH2 solutions with different concentrations in Example 1, after irradiation with 2 W / cm 2 , the temperature-time curves obtained after irradiation at 808 nm;
[0023] Figure 8 Colorimetric absorption spectrum (Figure a) and linear fitting curve (Figure b) of acrylamide;
[0024] Figure 9 Linear fitting curve of temperature sensing of acrylamide;
[0025] Figure 10 Results of the influence of interfering substances on the AM detection system;
[0026] Figure 11 Results of the influence of coexisting ions on the AM detection system. Detailed implementation manners
[0027] The content of the present invention will be further illustrated by the following examples, but these examples do not limit the protection scope of the present invention. The methods in the examples are all conventional methods without special instructions, and the reagents are all conventional commercially available reagents or reagents prepared according to conventional methods without special instructions;
[0028] Example 1: Determination of acrylamide in roasted coffee samples
[0029] 1. Preparation of Mxene
[0030] Add 1 g of LiF and 20 mL of 9 mol / L HCl solution into a polytetrafluoroethylene beaker. After stirring at 600 rpm for 1 h, slowly add 1 g of Ti3AlC2. After mixing evenly, continuously stir at 35 °C for 48 h, centrifuge at 4000 rpm for 10 min, wash the solid with pure water until the pH of the washing solution is 5, and then obtain Mxene after freeze-drying; perform transmission electron microscopy (TEM) analysis on Mxene, and the results are as Figure 1 shown. The synthesized Mxene has a 2D sheet structure, and lattice fringes with a spacing of 0.260 nm are presented in the high-resolution TEM (HRTEM) image of Mxene, which belong to the (101) crystal plane of MXene.
[0031] 2. Preparation of Mn / Fe-MIL-NH2
[0032] Dissolve 2 mmol of FeCl3·6H2O and 4 mmol of Mn(CH3COO)2·4H2O in 20 mL of DMF, denoted as solution A; simultaneously, dissolve 2 mmol of NH2-BDC in another 20 mL of DMF, denoted as solution B; subsequently, slowly add solution A to solution B and stir for 35 min to mix them evenly. Put the mixed solution into a Teflon autoclave, heat it at 120 °C for 10 h, cool it naturally, centrifuge at 6000 rpm for 10 min to obtain a light brown precipitate. Wash the precipitate 3 times each with DMF and absolute ethanol, centrifuge at 6000 rpm for 10 min, and dry the collected product at 80 °C for 12 h to obtain Mn / Fe-MIL-NH2.
[0033] 3. Preparation of Mxene@Mn / Fe-MIL-NH2 nanozyme
[0034] Mix 0.1 g of Mxene and 0.3 g of Mn / Fe-MIL-NH2 and disperse them in 50 mL of pure water, stir at room temperature for 7 h to obtain Mxene@Mn / Fe-MIL-NH2 nanozyme. Perform TEM analysis on the prepared Mxene@Mn / Fe-MIL-NH2, as Figure 2 shown. The synthesized Mxene@Mn / Fe-MIL-NH2 presents a typical hexagonal bipyramidal sample that grows and fuses uniformly on the surface of MXene. The lattice fringes with a spacing of 0.246 nm in the HRTEM image belong to the (103) crystal plane of MIL-53-NH2.
[0035] 4. Evaluation of peroxidase-like activity of Mxene@Mn / Fe-MIL-NH2 nanozyme
[0036] Mix 100 μL of 0.2 mmol / L TMB, 100 μL of 2 mmol / L H2O2, and 100 μL of 30 μg / mL Mxene@Mn / Fe-MIL-NH2 nanozyme solution, add 0.1 mmol / L phosphate buffer solution at pH 7.0 to 3 mL, shake well, let it stand for 10 min, and measure the absorbance at a wavelength of 654 nm. Figure 3 The results show that Mxene@Mn / Fe-MIL-NH2 nanozyme has good peroxidase-like activity; under the same conditions, add 100 μL of 50 μg / mL acrylamide (AM) and measure the absorbance. The results indicate that AM can significantly increase the absorbance of the reaction system.
[0037] In this example, the Michaelis catalytic kinetic parameters were also measured, and the results are shown in Figure 4 、 5 and Table 1. The Michaelis constants of Mxene@Mn / Fe-MIL-NH2 nanozyme for the substrates TMB and H2O2K m were 0.760 mmol / L and 0.528 mmol / L respectively, and the reaction rate constants were 5.721×10 -8 and 3.08×10 -8 mol / L·s. After adding AM, the K m concentrations of TMB and H2O2 were 0.164 mmol / L and 0.380 mmol / L respectively, and the reaction rate constants were 8.676×10 -8 and 7.618×10 -8 mol / L·s, indicating that the addition of AM greatly improved the affinity and reaction rate of Mxene@Mn / Fe-MIL-NH2 nanozyme with the substrates TMB and H2O2.
[0038] Table 1 Michaelis catalytic kinetic parameters
[0039] ;
[0040] Capture of free radicals: To further investigate the ROS that play a major role in the catalytic process, isopropanol (IPA), p-benzoquinone (PBQ), sodium oxalate (Na2C2O4), and silver nitrate (AgNO3) were used to capture ·OH, ·O2 - , h + and e - respectively. The results are shown in Figure 6 . After adding IPA, AgNO3, PBQ, and Na2C2O4, the absorbance values of oxidized TMB showed different decreasing trends. Among them, the decrease amplitude was the largest after adding IPA, followed by PBQ, indicating that the influence order was: ·OH > ·O2 - > h + > e - . These results indicate that ·OH and ·O2 - are the main ROS in the catalytic reaction.
[0041] 5. Photothermal performance evaluation of Mxene@Mn / Fe-MIL-NH2 nanozyme
[0042] Solutions containing different concentrations of Mxene@Mn / Fe-MIL-NH2 nanozyme were exposed to an 808 nm laser with a power of 2 W / cm 2 for 11 min, and the temperature changes were recorded. The results are shown in Figure 7 . It can be seen from the figure that as time increases, the solution temperature gradually rises. When the nanozyme concentration is 100 μg / mL, the highest solution temperature is 53.2 °C, indicating that Mxene@Mn / Fe-MIL-NH2 nanozyme exhibits excellent photothermal conversion ability after laser treatment.
[0043] 6. Preparation of acrylamide working curve
[0044] Add 100 μL of 0.2 mmol / L TMB, 100 μL of 2 mmol / L H2O2, 100 μL of 30 μg / mL Mxene@Mn / Fe-MIL-NH2 nanozyme, and acrylamide solution into a 5 mL stoppered colorimetric tube. Add 0.1 mmol / L phosphate buffer solution at pH 7.0 to 3 mL. The concentration of acrylamide in the reaction system is 0.095 - 85.7 μg / mL. Shake well and let stand for 10 min. Measure the absorbance at a wavelength of 654 nm. Plot the standard curve with the AM concentration as the abscissa and the absorbance value as the ordinate. The regression equation, correlation coefficient, relative standard deviation, linear range, etc. are shown in Table 2, and the results are shown in Figure 8 .
[0045] Meanwhile, add 100 μL of 0.2 mmol / L TMB, 100 μL of 2 mmol / L H2O2, 100 μL of 30 μg / mL Mxene@Mn / Fe-MIL-NH2 nanozyme, and acrylamide solution into a 5 mL stoppered colorimetric tube. Add 0.1 mmol / L phosphate buffer solution at pH 7.0 to 3 mL. The concentration of acrylamide in the reaction system is 0.05 - 85.0 μg / mL. After irradiating with an 808 nm NIR laser at a power of 2.0 W / cm 2 for 5 min, immediately use a portable pen-type digital thermometer to record the temperature and the increase value ΔT. Plot the standard curve with the AM concentration as the abscissa and the temperature increase value ΔT as the ordinate. The regression equation, correlation coefficient, relative standard deviation, linear range, etc. are shown in Table 2, and the results are shown in Figure 9 ; where ΔT = T - T0, and T and T0 are the temperatures of the reaction solution after and before laser irradiation, respectively.
[0046] Table 2 Linear equation, correlation coefficient, relative standard deviation, linear range
[0047] .
[0048] 7. Investigation of method specificity
[0049] Replace AM with other interfering substances (butyric acid (BA), 6 - aminohexanoic acid (EACA), acetic acid (AA), caffeic acid (CA), propionic acid (PA), glycine (Gly), L - aspartic acid (L - Asp), glucose (Glu)) and coexisting ions (Ca 2+ , Mg 2+ , Na + , K + , Fe 2+ , Fe3+ 、 HCO3 - 、 HPO4 2- ), the influence of other interfering substances on the Mxene@Mn / Fe-MIL-NH2 nanozyme catalytic system in the above detection system was detected. The final concentration of AM was 5 μg / mL, and the final concentration of the above interfering substances was 50 μg / mL; the results are shown in Figure 10 、 Figure 11 , it can be seen from the figure that only AM has a good enhancing effect on the Mxene@Mn / Fe-MIL-NH2 nanozyme catalytic system, and the results show that the nanozyme has good selective specificity for AM.
[0050] 8. Determination of acrylamide in roasted coffee samples
[0051] (1) Treatment of roasted coffee samples
[0052] After mixing 5.0 g (accurate to 0.01 g) of coffee powder with 20.0 mL of distilled water for 5 min, centrifuge in a 50 mL centrifuge tube at 8000 rpm for 10 min. After the sample extract is defatted with 20 mL of n-hexane, it is diluted 50 times with distilled water to reduce the sample matrix effect, and the sample extract is obtained;
[0053] (2) Detection of roasted coffee samples
[0054] Add 100 μL of 0.2 mmol / L TMB, 100 μL of 2 mmol / L H2O2, and 100 μL of 30 μg / mL Mxene@Mn / Fe-MIL-NH2 nanozyme to a 5 mL stoppered colorimetric tube, add 1 mL of the sample extract, and add 0.1 mmol / L pH 7.0 phosphate buffer solution to 3 mL. Shake well, let stand for 10 min, measure the absorbance at a wavelength of 654 nm, substitute the absorbance value into the regression equation in step 6, and the acrylamide content in coffee is 4.18 mg / kg;
[0055] At the same time, add 100 μL of 0.2 mmol / L TMB, 100 μL of 2 mmol / L H2O2, and 100 μL of 30 μg / mL Mxene@Mn / Fe-MIL-NH2 nanozyme to a 5 mL stoppered colorimetric tube, add 1 mL of the sample extract, and add 0.1 mmol / L pH 7.0 phosphate buffer solution to 3 mL. After the reaction system is irradiated with an 808 nm NIR laser with a power of 2.0 W / cm 2 for 5 min, immediately use a portable pen-type digital thermometer to record the temperature and calculate the increase value ΔT, and substitute ΔT into the regression equation in step 6. The acrylamide content in coffee is 4.01 mg / kg;
[0056] (3)Recovery and precision experiments: Standard acrylamide solutions with two different concentrations were added to roasted coffee samples; each concentration was determined in parallel 3 times, the spiked recovery rate was calculated, and the relative standard deviation RSD was calculated. The results are shown in Table 3. The spiked recovery rate of acrylamide was between 77.42% and 100.34%, and the RSD was between 0.74% and 3.21%. This method has good accuracy and precision.
[0057] Table 3 Spiked recovery rate and RSD of samples (n = 3)
[0058]
[0059] The method in Example 1 was compared with the national standard GB 5009.204-2014 National Food Safety Standard - Determination of Acrylamide in Foods. The results are shown in Table 4; it can be seen from the results that the results of the two methods are consistent.
[0060] Table 4 Method comparison results
[0061]
[0062] The acrylamide determination method established in the present invention has fewer treatment steps, is fast, simple, does not require large-scale instrument equipment and professional operators in GB 5009.204-2014, takes a short time, has a low treatment cost, is easy to operate, and has strong advantages in actual detection.
Claims
1. A method for the colorimetric and photothermal dual-mode detection of acrylamide in coffee based on MXene / MOFs nanozyme, characterized in that, The steps are as follows: (1) Add 1 - 2 g of LiF into 20 - 40 mL of 8 - 10 mol / L HCl solution. After stirring for 1 - 1.5 h, slowly add 1 - 2 g of Ti3AlC2. After mixing evenly, continuously stir at a temperature of 30 - 40 °C for 48 h, then centrifuge. Wash the solid with pure water until the pH of the washing liquid is 4 - 6, and then freeze-dry to obtain Mxene; (2) Dissolve 2 - 3 mmol of FeCl3·6H2O and 4 - 6 mmol of Mn(CH3COO)2·4H2O in 20 - 40 mL of DMF, denoted as solution A; at the same time, dissolve 2 - 3 mmol of NH2-BDC in 20 - 40 mL of DMF, denoted as solution B; then, slowly add solution A to solution B, stir and mix evenly. Heat the mixed solution at 120 - 140 °C for 8 - 10 h, let it cool naturally, then centrifuge to obtain a precipitate. Wash the precipitate 3 - 4 times with DMF and absolute ethanol respectively, then centrifuge, and dry the solid product to obtain Mn / Fe-MIL-NH2; (3) Mix Mxene and Mn / Fe-MIL-NH2 according to a mass ratio of 1:3 - 4, and disperse them in pure water. Stir at room temperature for 6 - 8 h to obtain the Mxene@Mn / Fe-MIL-NH2 nanozyme solution; (4) Add the Mxene@Mn / Fe-MIL-NH2 nanozyme solution into acrylamide solutions with different concentrations respectively, then add 3,3',5,5'-tetramethylbenzidine and H2O2, make up the volume to 3 mL with pH 7.0 phosphate buffer solution, shake well, let it stand for 5 - 10 min, and measure the absorbance at a wavelength of 654 nm to determine the linear relationship between the acrylamide concentration and the absorbance value; (5) Add the Mxene@Mn / Fe-MIL-NH2 nanozyme solution into acrylamide solutions with different gradient concentrations respectively, then add 3,3',5,5'-tetramethylbenzidine and H2O2, make up the volume to 3 mL with pH 7.0 phosphate buffer solution, shake well. After irradiating the reaction solution with 808 nm NIR laser for 4 - 6 min, use a portable pen-type digital thermometer to record the temperature and calculate the temperature change value ΔT, and determine the linear relationship between the acrylamide concentration and the temperature change value ΔT, where ΔT = T - T0, and T and T0 are the temperatures of the reaction solution after and before laser irradiation respectively; (6) Operate the test sample solution according to steps (4) and (5), measure the absorbance value and the temperature change value ΔT respectively, and obtain the acrylamide content in the test sample solution based on the absorbance value and the temperature change value ΔT.
2. The method according to claim 1, wherein: The concentration of the Mxene@Mn / Fe-MIL-NH2 solution is 30 μg / mL, the addition amount is 50 - 100 μL, the concentration of 3,3',5,5'-tetramethylbenzidine is 0.2 mmol / L, the addition amount is 50 - 100 μL, the concentration of H2O2 is 2 mmol / L, the addition amount is 50 - 100 μL, and the power of 808 nm NIR is 1.5 - 2.0 W / cm 2 .
Citation Information
Patent Citations
Method for rapidly detecting acrylamide in coffee
CN116559100A
Fe / PDA-Au-janus Ag-coated AuNPs combined aptamer dual-mode rapid acrylamide detection method
CN118961680A